Unstructured Peer-to-Peer Botnet Simulation for Measuring Its Robustness - Sayed Muchallil; Subhasish Dutta Chowdhuri; Kiran Venkatesh; Abhiram Doddaballapur Venkatraman; Candeep Singh (Jurnal Rekayasa Elektrika, 2011)
Malware attacks on the Internet have increasedsubstantially in recent years for which botnets are a root cause. A "botnet" is a network of compromised computers controlled by an attacker known as the "botmaster". To be able to effectively detect and defend against botnets, it is very important to have a good understanding of their construction procedure and propagation methodology. In this work, we study the construction of an unstructured peer-to-peer botnet, its propagation methodology, diurnal properties and robustness. This simulation shows that the more frequently a node updates its buddy list, the lesser is the process overhead involved.